PENGARUH LATIHAN ONE TOUCH CROSS AND FINISHING TERHADAP KEMAMPUAN KETEPATAN (ACCURACY) SHOOTING PADA TIM SSB UNRI U-17 - Arif Budi Darmawan; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract. Issues raised in this research is weak accuracy shooting when receiving passing or crossing when attacked, it looked when the players who receive passing or crossing then do the shooting still tend to widen laterally wicket, over the bar when playing. Then the results of interviews with coaches SSB UNRI concluded that the disadvantages experienced on SSB UNRI U-17 team is a weak player accuracy shooting. Purpose of this research to knowing influence one touch cross and finishing exercise, the ability accuracy shooting. Form of research with experimental (Experimental), with a population of soccer player SSB UNRI U-17, the data in this research is the entire population of 18 people. The instruments are made in the research is test shooting / kicking a ball into a goal (Shooting). After the data is processed with statistical, normality test to test the extent signifikat lilifor 0,05α. The hypothesis is effect of one touch cross and finishing exercise on the ability accuracy shooting. Based on t test analysis produces Tcalculated at 9.62 and Ttable at 1.740. Mean Tcalculated > Ttable. Earn in concluding that HI is received. With thus there is effect of one touch cross and finishing exercise on the ability accuracy shooting at SSB UNRI U-17 team.Key Words : One Touch Cross And Finishing Exercise, The Ability Accuracy Shooting